2020
DOI: 10.3390/plants9091128
|View full text |Cite
|
Sign up to set email alerts
|

Toward Unifying Global Hotspots of Wild and Domesticated Biodiversity

Abstract: Global biodiversity hotspots are areas containing high levels of species richness, endemism and threat. Similarly, regions of agriculturally relevant diversity have been identified where many domesticated plants and animals originated, and co-occurred with their wild ancestors and relatives. The agro-biodiversity in these regions has, likewise, often been considered threatened. Biodiversity and agro-biodiversity hotspots partly overlap, but their geographic intricacies have rarely been investigated together. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 105 publications
(163 reference statements)
2
36
0
1
Order By: Relevance
“…While biodiversity hotspots are mainly defined by species richness, agrobiodiversity hotspots refer to the centers of origin and diversity of (major) crops and their wild relatives, harboring genetic resources that are of high and increasing relevance for plant breeding. Pironon et al [8] observed spatial congruence between biodiversity and agrobiodiversity hotspots and proposed a unifying concept, taking into consideration not only species richness but also the multiple benefits plants offer to humankind in terms of ecosystem and agro-ecosystem functions, the inter-and intra-specific diversity of the chemical properties of plants for human nutrition and medicinal use, as well as the provision of gene sources for plant breeding. Rather than considering only major global food crops, agrobiodiversity conservation and use strategies should explicitly include the huge number of edible plants, which are currently underutilized and/or only of regional or often local importance, including wild food plants harvested in the wild that provide significant food and other benefits to humanity [19,20].…”
Section: Plant Biodiversitymentioning
confidence: 99%
See 4 more Smart Citations
“…While biodiversity hotspots are mainly defined by species richness, agrobiodiversity hotspots refer to the centers of origin and diversity of (major) crops and their wild relatives, harboring genetic resources that are of high and increasing relevance for plant breeding. Pironon et al [8] observed spatial congruence between biodiversity and agrobiodiversity hotspots and proposed a unifying concept, taking into consideration not only species richness but also the multiple benefits plants offer to humankind in terms of ecosystem and agro-ecosystem functions, the inter-and intra-specific diversity of the chemical properties of plants for human nutrition and medicinal use, as well as the provision of gene sources for plant breeding. Rather than considering only major global food crops, agrobiodiversity conservation and use strategies should explicitly include the huge number of edible plants, which are currently underutilized and/or only of regional or often local importance, including wild food plants harvested in the wild that provide significant food and other benefits to humanity [19,20].…”
Section: Plant Biodiversitymentioning
confidence: 99%
“…Several papers in this Special Issue have addressed genetic erosion aspects and provided suggestions and experiences regarding how this erosion can be stemmed for wild and cultivated biodiversity [8], CWR [3,21], wild food plants [19,20], vegetables [25], and forages [17].…”
Section: Genetic Erosionmentioning
confidence: 99%
See 3 more Smart Citations